Inventory and Enhancement of Geological Heritage in the Ouzoud Syncline (M’Goun UNESCO Geopark, Central High Atlas, Morocco): First Step for Promoting Geotourism and Sustainable Development - Elhassan Louz; Jamila Rais; Ahmed Barakat; Abdellah Ait Barka; Samir Nadem (Proceedings)
The Ouzoud syncline, in central Morocco, is one of the kingdom’s wealthiest areas of natural and cultural heritage. This syncline has significant potential for geotourism development; it contains the Ouzoud waterfalls, one of the most coveted tourist attractions, which are part of the geosites listed in the M’Goun UNESCO geopark. The abundance of resurgences, waterfalls, travertine, caves, magmatic rocks, exceptional geomorphological forms, and fascinating panoramic views make this territory a suitable tourist destination for excursions, hiking, and climbing, and a good support for understanding the geological history of the central High Atlas (CHA) of Morocco and paleoclimate changes. The dense and diversified vegetation cover offers a habitat for various animals (magot monkeys, bats, birds), which attracts more nature-loving tourists. This exceptional geo-biodiversity and cultural wealth (traditional mills and the Zaouïa of Tanaghmelt) that may constitute a lever for local socio-economic development remains unknown to the public and not well exploited by managers. Hence, this study attempted to assess and make an inventory of interest sites to provide a database that helps decision-makers in territorial planning and geoheritage conservation and promotion. Thus, about 20 highly attractive geosites were inventoried, eight of which (the most important ones) were selected for evaluation using the Reynard et al. (2016) methodology. This approach considers the scientific value, the additional values, and the use and management values of sites. Such promotion can popularize the geosciences and create income-generating activities, which will improve the economic situation of the local population